Omentum in the Pediatric Umbilical Hernia: Is It a Potential Alarm for the Appearance of Complications? - Xenophon Sinopidis; Antonios Panagidis; Vasileios Alexopoulos; Ageliki Karatza; Konstantina Mitropoulou; Anastasia Varvarigou; George Georgiou (Hindawi Limited, 2012)
Umbilical hernia is a common benign condition which resolves spontaneously during the first five years of life. However, in certain cases there are some characteristics which may be indicative of a different prognostic approach, as they increase the possibility of complications. The two cases of umbilical hernia that we describe here were treated operatively and revealed the presence of strangulated and adhered omentum, respectively. Reflecting on the adhesive properties of the omentum, we hypothesized that this may occur more often than it is believed, especially in those cases that are described as recurrent symptomatic herniations. In such cases, there should be increased alert for the possibility of complications during the period of the conservative expectance for resolution.